MUBALLIGH IN THE DIGITAL AGE BASED ON INSIGHTS FROM INDONESIAN PHENOMENON: LEVERAGING DIGITAL LEARNING FOR THE PROMOTION OF ISLAMIC VALUES - Choirin, Muhammad; Guleng, Marlon Pontino; Arbi, Dion Saputra; Maulan, Rikza (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2024)
Integrating digital technology in education has revolutionized learning across diverse fields, including religious education. This study explores how Islamic da'wah leverages digital platforms to enhance digital learning in the context of spreading da'wah in society, addressing challenges such as information accuracy, language barriers, and the balance between traditional and digital methods. Through a literature review and qualitative research, the study identifies and analyzes strategies employed by preachers to promote digital learning. The findings underscore the significant role of online platforms, mobile applications, online courses, e-learning, digital resources, virtual communities, and discussion forums in spreading Islamic da'wah in Indonesia. The substantial engagement with digital da'wah content from various Islamic teams highlights its impact. This research deepens understanding of the influence of digital learning on Islamic education, emphasizing its value as a complement to traditional face-to-face preaching. The study provides insights for Islamic preachers and educators, urging the refinement of digital learning initiatives to enhance the impact of Islamic education in contemporary contexts.